2016
DOI: 10.1111/jofo.12131
|View full text |Cite
|
Sign up to set email alerts
|

Breeding sites and winter site fidelity of Piping Plovers wintering in The Bahamas, a previously unknown major wintering area

Abstract: Most of the known wintering areas of Piping Plovers (Charadrius melodus) are along the Atlantic and Gulf coasts of the United States and into Mexico, and in the Caribbean. However, 1066 threatened/endangered Piping Plovers were recently found wintering in The Bahamas, an area not previously known to be important for the species. Although representing about 27% of the birds counted during the 2011 International Piping Plover Winter Census, the location of their breeding site(s) was unknown. Thus, our objectives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…These seasonal compensation effects, however, are positively correlated with the level of migratory connectivity or geographic linkage among populations (Norris & Marra, ). Plovers exhibit relatively high levels of site fidelity to both breeding and wintering locations (Friedrich et al., ; Gratto‐Trevor et al., ), but breeding populations show little connectivity with wintering populations (Gratto‐Trevor et al., ). Thus, the effects that we saw on wintering plovers from the previous season's reproductive output were unlikely to be related to density, but breeding propensity in subsequent years may have been related to density.…”
Section: Discussionmentioning
confidence: 99%
“…These seasonal compensation effects, however, are positively correlated with the level of migratory connectivity or geographic linkage among populations (Norris & Marra, ). Plovers exhibit relatively high levels of site fidelity to both breeding and wintering locations (Friedrich et al., ; Gratto‐Trevor et al., ), but breeding populations show little connectivity with wintering populations (Gratto‐Trevor et al., ). Thus, the effects that we saw on wintering plovers from the previous season's reproductive output were unlikely to be related to density, but breeding propensity in subsequent years may have been related to density.…”
Section: Discussionmentioning
confidence: 99%
“…Our data indicated that both male and female plovers that were not breeding were less likely to be detected, and that females were less likely than males, which may be further evidence that non-breeding birds tended to be more mobile. Many studies have affirmed the fidelity of plovers to locations across the annual cycle; fidelity of breeding birds to their populations (variously defined) across several studies was ≥83% and ≥46% for returning hatch year birds and appears to be relatively high for wintering birds as well (Gratto-Trevor et al 2016, Gibson et al 2018. Moreover, when plovers move, they do not disperse far; the median distance traveled between consecutive years and nests for plovers in this population was 153 m (Friedrich et al 2015).…”
Section: Discussionmentioning
confidence: 68%
“…Unmated males that are attempting to breed may be at greater risk of predation because of their conspicuous displays and aggressive territorial interactions (Elliot-Smith and Haig 2004). Many studies have affirmed the fidelity of plovers to locations across the annual cycle; fidelity of breeding birds to their populations (variously defined) across several studies was ≥83% and ≥46% for returning hatch year birds and appears to be relatively high for wintering birds as well (Gratto-Trevor et al 2016, Gibson et al 2018. Non-breeding female plovers, however, would presumably not have a territory and thus would be more mobile.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the unique geography of hundreds of islands combined with dozens of different political institutions poses a challenge to coordinated monitoring and reporting efforts. Third, few studies investigate shorebird use of Caribbean islands, and those that do tend to focus mainly on southern Puerto Rico (e.g., Parks, Collazo & Ramos-Alvarez, 2016a ; Parks, Collazo & Ramos-Alvarez, 2016b ; Wunderle, Waide & Fernandez, 2009 ) and Cuba (e.g., Nol et al, 2014 ), or specifically on Piping Plover (e.g., Johnson et al, 2018 ; Gratto-Trevor et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a 1985 paper about the status and distribution of Piping Plovers, it was noted that support for its distribution in the Caribbean was “sketchy at best” (p. 343) and cited a personal communication for suitable habitat in Cuba ( Haig & Oring, 1985 ). However, with the continued expansion of the International Piping Plover Census in the Caribbean, The Bahamas is now recognized as a major wintering area for the species, representing 27% of all birds counted in the census ( Gratto-Trevor et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%